Low cost visible light driven plasmonic Ag–AgBr/BiVO4 system: fabrication and application as an efficient photocatalyst1. Issue 50 (4th June 2015) - Sang, Yan; Huang, Yan; wang, Wu; Fang, Zhen; Geng, Baoyou
<x xml:space="preserve">Abstract</x> BiVO4 supported Ag–AgBr heterostructures were fabricated by a designed three-step method and then used as an efficient visible light driven plasmonic photocatalyst to degrade organic dye.